2021
DOI: 10.1038/s41438-021-00558-3
|View full text |Cite
|
Sign up to set email alerts
|

The diverse roles of cytokinins in regulating leaf development

Abstract: Leaves provide energy for plants, and consequently for animals, through photosynthesis. Despite their important functions, plant leaf developmental processes and their underlying mechanisms have not been well characterized. Here, we provide a holistic description of leaf developmental processes that is centered on cytokinins and their signaling functions. Cytokinins maintain the growth potential (pluripotency) of shoot apical meristems, which provide stem cells for the generation of leaf primordia during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 166 publications
(205 reference statements)
1
68
0
1
Order By: Relevance
“…In previous studies it is reported that, the HK3, HK4, and HK6 are cytokinin histidine kinase receptor related proteins, and WOX11 is the transcription factor involved in developmental processes. Similarly, CKX4 (cytokinin dehydrogenase) is a key enzyme involved in the catalyzation of the oxidation of cytokinin (Burr et al, 2020; Chen et al, 2020; Jiang et al, 2017; Wu et al, 2021). An in silico protein–protein interaction was performed among the OsARR‐B members and other cytokinin coregulatory proteins (Figure 6A and S1 and Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies it is reported that, the HK3, HK4, and HK6 are cytokinin histidine kinase receptor related proteins, and WOX11 is the transcription factor involved in developmental processes. Similarly, CKX4 (cytokinin dehydrogenase) is a key enzyme involved in the catalyzation of the oxidation of cytokinin (Burr et al, 2020; Chen et al, 2020; Jiang et al, 2017; Wu et al, 2021). An in silico protein–protein interaction was performed among the OsARR‐B members and other cytokinin coregulatory proteins (Figure 6A and S1 and Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Cytokinins play a crucial role in regulating plant growth and development. They can promote the proliferation and expansion of leaf cell development and coordinate with auxins to regulate plant growth [ 32 ]. In our study, two genes related to the response regulation of Arabidopsis were upregulated in strongly dominant hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the PGPR which synthesize cytokinin includes Pseudomonas stutzeri, Stenotrophomonas maltophilia and P. putida. Cytokinin is involved in the maintenance of plant cell division in culture and in various differentiation processes such as primary root growth, callus formation and shoot formation (43,44). Totipotency is the distinguishing feature of cytokinin from other plant growth regulators, which helps to maintain totipotent stem cells in their root and shoot meristem.…”
Section: Phytohormone: Cytokininmentioning
confidence: 99%